2013
DOI: 10.1111/ajsp.12027
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status, perceived parental control, and authoritarianism: Development of authoritarianism in Iranian society

Abstract: The purpose of the current study is to examine the relationship between socioeconomic status, parental control, and authoritarianism in Iran. A sample of 460 students was surveyed from Shahid Chamran University of Ahvaz in Iran. Results demonstrated that subjective socioeconomic status, parental control, and parents' education have significant influence on authoritarianism. Further analysis showed that parental control partially mediates parents' education association with authoritarianism with a relatively hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 56 publications
4
7
0
Order By: Relevance
“…It was found that SES has a significant effect on parental control. Members of higher SES perceived lower level of authoritarian control from their parents and this finding is consistent with other studies as well (e.g., Gecas, 1979;Heimer, 1997;Heydari et al, 2013;Kohn, 1977;Kohn & Schooler, 1969). In addition, authoritarian parental control can lead to the feeling of anomie.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was found that SES has a significant effect on parental control. Members of higher SES perceived lower level of authoritarian control from their parents and this finding is consistent with other studies as well (e.g., Gecas, 1979;Heimer, 1997;Heydari et al, 2013;Kohn, 1977;Kohn & Schooler, 1969). In addition, authoritarian parental control can lead to the feeling of anomie.…”
Section: Discussionsupporting
confidence: 90%
“…For the reliability, alpha Cronbach of .80 was obtained. Heydari et al (2013) used the Perceived Parental Control and found Alpha reliability of 0.85 as well.…”
Section: Perceived Parental Control Scalementioning
confidence: 99%
“…People of middle and lower SES experience more dissatisfaction in anomic conditions since they have limited resources compared to the upper classes. Similar relationships between anomie and SES have been reported in other studies (Bell, 1957;Heydari, 2010;Heydari et al, 2012Heydari et al, , 2013Lee & Clyde, 1974;Menard, 1995;Mizruchi, 1960;Rushing, 1971;Teevan, 1975).…”
Section: Ses and Feelings Of Anomiesupporting
confidence: 85%
“…Similarly, insecure parent-child attachment is also more common in lower SES families and promotes authoritarian traits in children (Oesterreich, 2005;Owens-Sabir, 2007;Weber & Federico, 2007). Research in Iran also suggests that both parenting style and authoritarian patterns are widespread in lower SES Iranian families (for a review see Heydari et al, 2013).…”
Section: Relationship Of Ses With Authoritarianismmentioning
confidence: 99%
“…Five criminology and sociology experts confirmed the face validity of the scale and internal reliability of .83 was also obtained (Heydari et al, 2012). In addition, the scale was shown to have significant relationships with external source of moral reasoning (Teymoori et al, 2012), perceived parental control (Heydari et al, 2013), ethnocentrism (Heydari et al, in press), and anomie and socioeconomic status (Heydari et al, 2012), which is consistent with the literature and confirms the content validity of the scale.…”
Section: Methodssupporting
confidence: 84%